Learning with ABC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The African Books Collective is a self-help initiative by a group of African publishers to promote their books in Europe, in North America and in Commonwealth countries outside Africa. ABC is represented by publishers on a broad regional basis...